THE INFLUENCE OF REWARD SYSTEM ON EMPLOYEE JOB SATISFACTION WITH WORK MOTIVATION AS INTERVENING VARIABLES (Case Study on Employees of Medical Department United States) - Stephen Martinr; Martin Uribe (PT. Radja Intercontinental Publishing, 2021)
This study aims to determine“The Influence of the Reward System on Employee Job Satisfaction with Work Motivation as an Intervening Variable (Case Study of Employees of Medical Department United States)